Assessing introduced Leguminosae in Mexico to identify potentially high-impact invasive species - Sánchez-Blanco, Judith; Sánchez-Blanco, Clara; Sousa S., Mario; Espinosa-García, Francisco J. (Instituto de Ecología, A.C., 2012)
Most introduced plant species in Mexico have not been assessed to prioritize management actions to eradicate or contain them, or for damage mitigation after plant invasions. We assessed 42 introduced weed taxa in the Leguminosae using empirical and theory derived criteria in a model focused in the species behavior abroad, their residence time and number of occupied localities, and the presence in Mexico of closely related relatives (native and non-native) at the genus level. Data were obtained from bibliographic sources and from the “Malezas Introducidas en México” database, which includes information from 11 Mexican herbaria. We also developed a scoring process to qualify introduced weed expansion using residence time and number of occupied localities. We classified the analyzed introduced legumes in four priority of attention categories. We suggest that Albizia lebbeck, Pueraria phaseoloides, Lablab purpureus, Securigera varia, Delonix regia, Clitoria ternatea, and Spartium junceum should receive high-priority attention; eight species were considered to require medium priority attention; seven low priority attention, and 20 taxa were classified as non-priority. The developed assessment model still needs further refinement, as seemingly innocuous species scored high and a potentially dangerous species (Cassia fistula) were classified in the non-priority category. We hope that this assessment model will work as a structured, low expert-dependent approach to identify the introduced species that require a further risk analysis to prioritize efforts for noxious plant management.